Cytokines, Autoantibodies, and Complements in Active Systemic Lupus Erythematosus Patients from Javanese Population - Yuliasih Yuliasih; Lita Diah Rahmawati; Putu Ayu Niken Amrita; Setiati Widyaningrum; Dodi Kriswanto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease that has various clinical manifestations. The SLE pathogenesis involves both innate and adaptive immunological components. The system is essentially determined by genetic factors that control certain clinical and serological manifestations. Genetic traits that determine the roles of cytokines, autoantibodies, and complements in SLE vary among ethnicities. The roles of TNF-Î±, IL-6, anti-C1q, anti-dsDNA, C3, and C4 towards SLE activity need to be evaluated in the Javanese population. This study aimed to determine the correlation of TNF-Î±, IL-6, anti-C1q antibodies, anti-dsDNA, C3, and C4 with SLE activity. Forty SLE patients were diagnosed based on the American College of Rheumatology (ACR) criteria. Disease activity was measured by the Systemic Lupus Activity Measure (SLAM) index. TNF-Î±, IL-6, Anti-C1q, and anti-dsDNA levels were measured by ELISA, while MINIMEPH measured C3 and C4. Thirty-nine female and one male patient with SLE were diagnosed according to ACR criteria. The mean of SLAM score, anti-dsDNA, C3, and C4 levels was 20.98±6.7, 224.96±298.6, 68.70±37.08 mg/dL, and 18.75±10.69 mg/dL, respectively. Spearman's correlation test showed a positive correlation between TNF-Î± (r = 0.971, p<0.001), IL-6 (r=0.835, p<0.001), anti-C1q (r=0.399, p=0.01), and disease activity (SLAM score) by using. The linear regression test for TNF-Î±, IL-6, anti-C1q, and SLAM showed the strongest association for TNF-Î± (r=0.891, p<0.000). TNF-Î±, IL-6, and anti-C1q were correlated to disease activity in SLE patients from the Javanese population.